Global strong solution of 2D Navier–Stokes–Korteweg system. (10th May 2021) - Yu, Yanghai; Wu, Xing
Abstract : In this paper, we consider the Cauchy problem to the two‐dimensional Navier–Stokes–Korteweg system with nonvacuum and general pressure laws and establish the global well‐posedness of strong solution for general initial data in the framework of Sobolev spaces.